The 21st Century Nuclear Dilemma: Between Deterrence and Proliferation - Morales, César (2025)
This article analyzes the evolution of atomic technology for military use, from its birth in the Manhattan Project to the complex current situation of nuclear weapon proliferation and modernization. It examines how the disasters of Hiroshima and Nagasaki redefined warfare, giving rise to the Cold War and the doctrine of Mutually Assured Destruction, which maintained a precarious peace based on the fear of annihilation. The paper distinguishes between vertical proliferation by the original nuclear powers and horizontal proliferation by new states that have developed nuclear weapons, analyzing the challenges to disarmament agreements such as the Treaty on the Non-Proliferation of nuclear weapons. It then describes some critical moments, such as when the Soviet Union installed missiles with nuclear warheads in Cuba, a time when the world was on the brink of an atomic catastrophe. The article also addresses proliferation outside the international legal framework, with countries like India, Pakistan, North Korea, and Israel developing nuclear arsenals without adhering to global agreements. Finally, it evaluates the contemporary state of global nuclear material, discussing whether the current modernization of arsenals leads to greater deterrence or is instead paving the way toward mutual destruction.